Optics and Spectroscopy - Aleksandrov, Evgenii B.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Optics and Spectroscopy (Optika i spektroskopiya), founded in 1956, presents original and review papers in various fields of modern optics and spectroscopy in the entire wavelength range from radio waves to X-rays. Topics covered include problems of theoretical and experimental spectroscopy of atoms, molecules, and condensed state, lasers and the interaction of laser radiation with matter, physical and geometrical optics, holography, and physical principles of optical instrument making.
Keywords: Lasers; Photonics; Optics, Lasers, Photonics, Optical Devices